2011
DOI: 10.1007/s00420-011-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout risk in medical students in Spain using the Maslach Burnout Inventory-Student Survey

Abstract: The Maslach Burnout Inventory-Student Survey overcame difficulties encountered when students have little or no contact with patients. Our findings show that the risk of burnout prevalence doubled from the third year to sixth year of training and that gender was not significantly associated with any of the subscales of burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
6
29

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(188 citation statements)
references
References 24 publications
12
141
6
29
Order By: Relevance
“…For example, some studies reported low reliabilities for the subscales (Galán et al, 2011). In other cases (Gumz et al, 2013;Hu & Schaufeli, 2009), although the three-factor model was replicated in student samples, the statistical strategy that was adopted raised serious methodological and statistical concerns (i.e., error terms had to be correlated for at least two items in order to achieve satisfactory fit).…”
Section: Academic Burnoutmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, some studies reported low reliabilities for the subscales (Galán et al, 2011). In other cases (Gumz et al, 2013;Hu & Schaufeli, 2009), although the three-factor model was replicated in student samples, the statistical strategy that was adopted raised serious methodological and statistical concerns (i.e., error terms had to be correlated for at least two items in order to achieve satisfactory fit).…”
Section: Academic Burnoutmentioning
confidence: 97%
“…Several studies translated the MBI-SS into other languages (Galán, Sanmartín, Polo, & Giner, 2011;Gumz, Erices, Brähler, & Zenger, 2013;Hu & Schaufeli, 2009), without, however, being able to clearly justify its psychometric qualities. For example, some studies reported low reliabilities for the subscales (Galán et al, 2011).…”
Section: Academic Burnoutmentioning
confidence: 98%
“…A kiégés alacsony, közepes és magas szintjét a Galán, Sanmartín, Polo és Giner [27] által javasolt ponthatárok alapján szá-moltuk ki. Az eredményeket az 1. táblázat mutatja be.…”
Section: Az Orvostanhallgatók Közel Fele Magas Szintű Kiégésről Számounclassified
“…In the Turkish MBI-SS, students indicate their burnout level on a 5-point frequency scale (1= never, 5= always); high scores on exhaustion and cynicism and low scores on efficacy subscales indicate high level of burnout (Çapri et al, 2011). To measure the burnout level of students in the present study, only exhaustion and cynicism subscales were used, as previous studies (Bresó et al, 2011;Galánet al, 2011;Mostert et al, 2007;Salanova et al, 2010;Skaalvik and Skaalvik, 2010) have suggested these two dimensions are core elements of burnout.…”
Section: Mbi-ssmentioning
confidence: 99%